La vigencia de la doctrina Monroe a doscientos años de su enunciación - Rodríguez Orozco, Alán Ricardo (El Colegio de México A.C., 2024)
This article examines the enduring relevance of the Monroe Doctrine in U.S. foreign policy toward the Americas, two hundred years after its formulation. Adopting a world-systems analysis perspective, it argues that the Doctrine has persisted as a mechanism for U.S. intervention in the region. To support this claim, the article reviews continuities and similarities in the foreign policies of three U.S. presidents whose policies and styles are often seen as antithetical. The study identifies three areas of continuity in the deployment of the Doctrine: the containment of Russian and Chinese influence, the militarization of counternarcotics efforts as a means of regional intervention, and opposition to national-populist governments. It concludes that variations in the implementation of the Monroe Doctrine reflect tactical and situational adjustments rather than substantive changes in the principles guiding U.S. foreign policy toward the Americas.